The Impact of School Climate on Emotion Regulation in Indonesian Students: Evidence from PISA 2022 - Tarmidi Dadeh; Glory Hutasoit; Muhammad Rozan Alfarisi; Shafqat Rasool (Journal An-Nafs: Kajian Penelitian Psikologi, 2025)
Adolescence is a critical developmental period marked by significant changes, during which individuals must cultivate emotional intelligence to navigate academic pressures, social relationships, and potential negative behaviors. A positive school climate is key to fostering effective adolescent emotion regulation. This study presents a novel investigation into the role of school climate in shaping emotion regulation among Indonesian students, using nationally representative data from the post-pandemic PISA 2022 assessment. Employing a quantitative approach, the study draws on data from 13,439 students across Indonesia. A multiple linear regression analysis assessed the relationship between school climate and emotion regulation, yielding a significant model, F(4, 12,286) = 129.297, p < .001, R² = .040. The findings indicate that school climate significantly influences students’ emotion regulation. Specifically, a sense of belonging, experiences of bullying, and feelings of safety were found to be significant predictors, while school safety risk was not statistically significant. By exploring this underexamined link in the Indonesian context—particularly through the lens of PISA 2022—the study provides timely, evidence-based insights into how school environments can support adolescents’ emotional development. The results underscore the importance of fostering inclusive, safe, and supportive school climates to enhance students’ emotional well-being and self-regulatory skills. This research offers new theoretical and policy-relevant contributions to the literature on educational psychology and adolescent mental health.